2016
DOI: 10.1371/journal.pone.0165062
|View full text |Cite
|
Sign up to set email alerts
|

Platinum(II) Iodido Complexes of 7-Azaindoles with Significant Antiproliferative Effects: An Old Story Revisited with Unexpected Outcomes

Abstract: A series of platinum(II) diiodido complexes containing 7-azaindole derivatives, having the general formula cis-[PtI2(naza)2] (1–8), has been prepared and thoroughly characterized, including X-ray structure analysis of cis-[PtI2(2Me4Claza)2]∙DMF (8∙DMF; 2Me4Claza = 2-methyl-4-chloro-7-azaindole). Complexes showed high in vitro cytotoxicity against nine human cancer cell lines (IC50 ranging from 0.4 to 12.8 μM), including the cisplatin-resistant ovarian cancer cell line (A2780R; IC50 = 1.0–3.5 μM). The results o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 49 publications
(76 reference statements)
4
11
0
Order By: Relevance
“…4 Another example is the work performed by Dvořák et al., varying the amine ligand and substituting for bulkier azaindoles. 5 They studied the cytotoxic activity of iodide azaindole complexes and looked at the molecular level mechanism to find a decrease of tumor suppressor p53 amount, which can agree with our previous observations with the aliphatic amine iodido compounds. 6…”
Section: Introductionsupporting
confidence: 76%
“…4 Another example is the work performed by Dvořák et al., varying the amine ligand and substituting for bulkier azaindoles. 5 They studied the cytotoxic activity of iodide azaindole complexes and looked at the molecular level mechanism to find a decrease of tumor suppressor p53 amount, which can agree with our previous observations with the aliphatic amine iodido compounds. 6…”
Section: Introductionsupporting
confidence: 76%
“…Cis-Pt(II) iodido complexes have long been predominantly used as intermediates in synthesizing target platinum chlorides and carboxylates, particularly by the Dhara method or its modifications [17,18]. However, later several studies have shown that the iodido ligand may have unique chemical, physical, and biological properties, with a mechanism of action different from that of Pt(II) chlorido analogs [19][20][21][22]. For example, cis-Pt(II) diiodides containing 7-azaindole and its derivatives were significantly more active than cisplatin in several cancer cell lines [19].…”
Section: Introductionmentioning
confidence: 99%
“…However, later several studies have shown that the iodido ligand may have unique chemical, physical, and biological properties, with a mechanism of action different from that of Pt(II) chlorido analogs [19][20][21][22]. For example, cis-Pt(II) diiodides containing 7-azaindole and its derivatives were significantly more active than cisplatin in several cancer cell lines [19].…”
Section: Introductionmentioning
confidence: 99%
“…Morevoer, these last trans series seemed to be affected by the size of the amine ligands showing differences in their reactivity versus S-donor models and in their cytotoxicity [6]. The reconsideration of these iodido derivatives have shown a great impact in the field, and the trend and behavior of these complexes is being reevaluated [7].…”
Section: Introductionmentioning
confidence: 99%